PENGARUH KOMPENSASI, MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PUSKESMAS SEMEMI - Maria Flavianey Noni; Mochammad Syaiful Arif (Fakultas Ekonomi dan Bisnis Universita Wijaya Putra Surabaya, 2024)
this study aims to determine the descreption of compensation, motivation and work environment on employee performance at Sememi Health Center, Determine the effect of compencation on employee perfonmance at Sememi Health Center, Determine the effect of motivation on employee performance at Sememi Health Center, determine the effect of work environment on employee performance at Sememi Health Center, Determine the effect of compensation, motivation, and work environment on employee performance at Sememi Health Center. This research is a comparative causal research with a quantitative approach which research. The total population was 41 people, all populations were used as responden in the study with the saturated sampling methode. This research was obtained by distributing questionnaires to employees. Prerequisite testing of analysis using validity test and reliability test. The data analysis technique used is multiple linear regression using the SPSS 21 program. The results of this study indicate that the compensation variable partially has no significant effect on employee performance, motivation partially has no significant effect on employee performance and the work environment partially has a significant effect on employee performance, while compensation, motivation and work environment simultaneously have a significant effect on employee performance.